A review of material, design, and techniques in 3D printing for medical applications - Mohamad Sazri Fahmi, Ramli; Muhammad Hazli, Mazlan; Takano, Hiromitsu; Abdul Halim, Abdullah; Muhammad Hilmi, Jalil (International Association of Online Engineering, 2023)
This review research assesses the numerous 3D printing methods utilized in medical applications and the materials and design methods that are associated with the current and existing technology. The article thoroughly examines the advantages and disadvantages of various techniques and materials and the difficulties of applying 3D printing technology to the medical sector. Further research and development are required to overcome current challenges since the review highlights the importance of design strategies in achieving positive medical outcomes. Overall, the article provides a thorough overview of the state of 3D printing in medical applications today and its potential to revolutionize the industry.